PERCEPTION ABOUT USE OF ARTIFICIAL INTELLIGENCE APPLICATIONS IN FORENSIC MEDICINE AMONG TEACHING FACULTIES AND POSTGRADUATE STUDENTS OF FORENSIC MEDICINE -A QUESTIONNAIRE-BASED STUDY - Kumar J, Sasi; Vaswani, Vina Ravi; Shenoy, Venkatkrishna (Journal of Forensic Medicine and Toxicology, 2025)
Forensic Medicine traditionally relies on manual analysis by Forensic doctors, which can be time-consuming and influenced by personal biases. However, technology such as Artificial Intelligence (AI) has introduced new possibilities to this field. The study explores how teaching faculty and post graduate students of Forensic Medicine in selected institutions within India, perceive and utilize artificial intelligence in Forensic investigations. After review of articles regarding the uses of artificial intelligence in Forensic discipline and practices, a questionnaire was created, and distributed to teaching faculty and postgraduate students of Forensic Medicine for insights into their understanding and perspectives on artificial intelligence. The study participants consisted of Forensic Medicine teaching faculty of 61 in numbers and 35 postgraduate students, a total of 96 participants in which various perceptions about Artificial intelligence were explored. The majority of participants acknowledged the potential of Artificial intelligence to enhance efficiency in Forensic investigations, envisioning its use in conferences, research, solving complex cases,and highlighted its application in virtopsy, DNA analysis and recognizing injury patterns. Nearly 50% of the participants disagreed regarding inaccuracy of Artificial intelligence application in Forensic investigations. The cost for implication of Artificial intelligence in Forensic investigations was considered expensive by nearly 70% of the participants. More than half of the participants lack knowledge regarding Artificial intelligence application in drug abuse, detecting traumatic brain injury. For effectively integrating Artificial intelligence into Forensic practice, awareness of Artificial intelligence application in Forensic research is essential. A clear guideline is required to uphold ethical principles in the use of Artificial intelligence in teaching and learning. More so, exploring Artificial intelligence usage to gain knowledge could help reduce workload, time constraint and improve precision and accuracy in Forensic investigation.
Keywords: Artificial intelligence; Forensic Medicine; machine learning; neural network